Schriftexegese als Voraussetzung für Emil Brunners Dialogik anhand des Beispiels Jes 6,1–13 - Fabienne STEINER (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica)
Dialogics Using the Example of Isa 6,1–13. In my article, I would like to discuss Emil Brunner’s early thoughts and statements, which he says in his sermons in Obstalden. These sermons are still unknown and unpublished. It is mostly claimed that Brunner entered in a dialectical phase because of his colleague in the Reformed Church, Karl Barth. It is true that they later had intense discussions about theses and antitheses in this dialectical process. Brunner, however, comes up with new dialectical thoughts, for example, on dialogics of “I and Youˮ earlier than in his discussion with Barth and writes a sermon with the same title. On the example of Isa 6,1–13, I will discuss a few statements of Brunner from Obstalden. Back then, he already emphasized the personal correspondence between dialogics of God (You) and man (I).